(untitled) (Journal of Economic Research & Business Administration, 2018)
The economic consequences of regional integration are significant to the debate in Europe, the United States and other countries around the world. The purpose of this study is to identify, on the basis of research papers by foreign and domestic scientists, the positive and negative consequences of the regional economic integration and the assessment of their manifestation in the economy of the EAEU countries. The scientific and practical significance of the work is as follows. Despite many years of experience in world economic integration, there is still no consensus on the prevalence of positive or negative effects of integration. We have studied and summarized a large theoretical and practical material on the consequences of the regional integration and analyzed data on the member countries of the EAEU. The analysis showed that membership in the EAEU has not yet shown significant positive effects for partner countries. The dynamics and trends in the growth of integration effects in the EAEU cause some concern. However, the reasons for these processes lie not in the group itself, but rather in the unfavorable situation on the world market. The fall in the world market for oil and gas prices and the impact of currency fluctuations on the market. Of course, all this has affected the domestic economic situation in the partner countries. Since 2017, there has been a recovery in economic growth. In connection with the growth of the economy for all countries will be characterized by the restoration of consumer demand. One of the factors of growth will be investment activity in the EAEU states. Conditions for increasing the investment activity of the private sector will be created, including through price stabilization. Thus, summing up the results of our research, we hope that it will contribute to the scientific literature on the problems of regional economic integration, proving a new approach to determining its effects. Our results show that economic integration is not a zero-sum game and can be mutually beneficial for partner countries.